2017
DOI: 10.1111/jcpe.12742
|View full text |Cite
|
Sign up to set email alerts
|

Addition of enamel matrix derivatives to bone substitutes for the treatment of intrabony defects: A systematic review, meta‐analysis and trial sequential analysis

Abstract: In the treatment of intrabony defects, the addition of EMD to BS seems to be not beneficial in terms of CAL gain, PD reduction and REC changes. However, such results should be considered with caution because of the small number of studies included in the meta-analysis and their heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…These results may indicate that: (1) in the treatment of 3–wall defects, the sole use of rhFGF‐2 may be sufficient; (2) a greater level of healing can be expected by adding DBBM in more challenging cases such as deeper defects or 1– to 2–wall defects. In some studies, no additional benefits in clinical outcomes were found regarding the use of EMD with bone substitutes (Hoffmann et al, 2016; Kao et al, 2015; Troiano et al, 2017). Potential benefits of adding various bone substitutes to rhFGF‐2 therapy and indications need to be verified by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results may indicate that: (1) in the treatment of 3–wall defects, the sole use of rhFGF‐2 may be sufficient; (2) a greater level of healing can be expected by adding DBBM in more challenging cases such as deeper defects or 1– to 2–wall defects. In some studies, no additional benefits in clinical outcomes were found regarding the use of EMD with bone substitutes (Hoffmann et al, 2016; Kao et al, 2015; Troiano et al, 2017). Potential benefits of adding various bone substitutes to rhFGF‐2 therapy and indications need to be verified by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In particular, considering the results of periodontal treatment performed on the three-wall intrabony defects, OFD with EMD alone or OFD with EMD combined with other biomaterials (including barrier membrane and grafting material) showed more favorable clinical, radiographic, and histological outcomes when compared with the results from the use of OFD alone. 31,32 Adjunctive use of bone grafting material with EMD led to a statistically significant PD reduction and CAL gain, and promoted filling of the defect with newly formed bone when compared with the cases where OFD with EMD or with bone grafting alone was used for the treatment of intrabony defects. 14,26,33 Despite these favorable outcomes, systematic reviews and meta-analyses involving one-, two-, and threewall intrabony defects concluded that the treatment of intrabony defects with the adjunctive use of EMD in combination with bone grafting material did not result in clinically or radiographically superior results over that from the use of OFD with bone grafting.…”
Section: Discussionmentioning
confidence: 99%
“…The search was complemented by a screening of the Open Grey database and of the reference lists of included studies and previous systematic reviews or guidelines dealing with regenerative surgical procedures for the treatment of periodontal intra‐bony defects (Cãlin & Pãtraşcu, ; Castro et al, ; Darby & Morris, ; Del Fabbro, Bortolin, Taschieri, & Weinstein, ; Esposito et al, ; Giannobile & Somerman, ; Graziani et al, ; Hou, Yuan, Aisaiti, Liu, & Zhao, ; Kao, Nares, & Reynolds, ; Khojasteh, Sogeilifar, Mohajerani, & Nowzari, ; Khoshkam et al, ; Koop, Merheb, & Quirynen, ; Matarasso et al, ; Miron et al, ; Murphy & Gunsolley, ; Needleman et al, ; Pagliaro et al, ; Panda, Doraiswamy, Malaiappan, Varghese, & Fabbro, ; Parrish, Miyamoto, Fong, Mattson, & Cerutis, ; Patel, Wilson, & Palmer, ; Rathe, Junker, Chesnutt, & Jansen, ; Reynolds, Aichelmann‐Reidy, Branch‐Mays, & Gunsolley, ; Roselló‐Camps et al, ; Sculean et al, ; Stoecklin‐Wasmer et al, ; Troiano et al, ; Trombelli, Heitz‐Mayfield, Needleman, Moles, & Scabbia, ; Yen, Tu, Chen, & Lu, ; Zanatta, Souza, Pinto, Antoniazzi, & Rösing, ; Zhou et al, ).…”
Section: Methodsmentioning
confidence: 99%